A plataformização dos sujeitos e a comunicação com o ambiente e com outras espécies: uma experiência de sensibilização fora das telas na Unidade de Conservação RPPN Lafigueira – Piracaia/SP - Vieira, Rodrigo (2024)
This dissertation investigates the impact of the relationships between different forms of life (plants, animals, plants) on contemporary behavior described here as the platformization of subjects, which is produced by the intensity of the use of screens. It is based on a personal experience of monitoring work carried out in a conservation unit - UC Lafigueira, in Piracaia/SP - which is part of a Private Natural Heritage Reserve (RPPN). It proposes as theoretical axes the Corpomedia Theory (Katz; Greiner), recent bibliographies on other species (Massumi; Mancuso; Coccia; Simard; Wohlleben; Despret) and the concept of the common (Dardot; Laval). The hypothesis is that getting closer to other, non-human life, such as trees, birds, bees and bats, can reduce the damage caused by platformization, raising awareness of the commitment to ecology and reducing the current situation of illness that has been established. The aim was to present a critical reflection on the relationship between people who are disinterested in environmental and consumer issues and the use they make of screens, demonstrating the urgency of raising awareness of processes that directly and indirectly contribute to the continuity of life. To this end, the research brought together a bibliographical review and a selection of six studies carried out in the Atlantic Forest, at the Lafigueira Conservation Unit. Proposing a broader reflection on this complex debate is urgent